Insurance and Behavioral Economics : Improving Decisions in the Most Misunderstood Industry - Kunreuther, Howard; Pauly, Mark V., 1941-; McMorrow, Stacey (Cambridge : Cambridge University Press, 2013)
This book examines the behavior of individuals at risk and insurance industry decision makers involved in selling, buying and regulation. It compares their actions to those predicted by benchmark models of choice derived from classical economic theory. Where actual choices stray from predictions, the behavior is considered to be anomalous. Howard C. Kunreuther, Mark Pauly and Stacey McMorrow attempt to understand why these anomalies occur, in many cases using insights from behavioral economics. The authors then consider if and how such behavioral anomalies could be modified to improve individual and social welfare. This book describes situations in which both public policy and the insurance industry's collective posture need to change. This may require incentives, rules and institutions to help reduce both inefficient and anomalous behavior, thereby encouraging behavior that will improve individual and social welfare.
Machine generated contents note: 1. Purposes of this book; 2. An introduction to insurance in practice and theory; 3. Anomalies and rumors of anomalies; 4. Behavior consistent with benchmark models; 5. Real world complications; 6. Why people do or do not demand insurance; 7. Demand anomalies; 8. Descriptive models of insurance supply; 9. Anomalies on the supply side; 10. Design principles for insurance; 11. Strategies for dealing with insurance-related anomalies; 12. Innovations in insurance markets through multi-year contracts; 13. Publicly-provided social insurance.
Title from publisher's bibliographic system (viewed on 05 Oct 2015).
Keywords: Risk (Insurance); Insurance -- Decision making; Consumer behavior